Aesthetics, applications, artistry and anarchy : essays in prehistoric and contemporary art : a festschrift in honour of John Kay Clegg, 11 January 1935 - 1 March 2015 /: essays in prehistoric and contemporary art : a festschrift in honour of John Kay Clegg, 11 January 1935 - 1 March 2015. (2019) - Unknown
No abstract available